2021
DOI: 10.1111/his.14360
|View full text |Cite
|
Sign up to set email alerts
|

Dysplasia and carcinoma of the gallbladder: pathological evaluation, sampling, differential diagnosis and clinical implications

Abstract: Pathological evaluation of gallbladder neoplasia remains a challenge. A significant proportion of cases presents as clinically and grossly inapparent lesions, and grossing protocols are not well established. Among epithelial alterations, pseudo‐pyloric gland metaplasia is ubiquitous and of no apparent consequence, whereas goblet cell metaplasia and a foveolar change in surface cells require closer attention. Low‐grade dysplasia is difficult to objectively define and appears to be clinically inconsequential by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 67 publications
0
44
0
3
Order By: Relevance
“…The studies have shown its incidence ranging from 0.2%-3.3%. [ 1 , 4 , 9 - 11 , 24 ]. Out of the total who received cholecystectomies during the study period, 11 GBC (11/1253; 0.87%) were diagnosed incidentally in our study, which was in accordance with the published literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies have shown its incidence ranging from 0.2%-3.3%. [ 1 , 4 , 9 - 11 , 24 ]. Out of the total who received cholecystectomies during the study period, 11 GBC (11/1253; 0.87%) were diagnosed incidentally in our study, which was in accordance with the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Gallstones are the major co-morbid risk factors seen in 70-98% of GBC cases with an incidence of GBC related to cholelithiasis ranging from 0.3% to 12%. [ 2 , 4 , 7 , 11 , 17 - 19 ]. Estrogen causing increased cholesterol super-saturation in the bile has been attributed to the gallstone-mediated GBC pathogenesis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical characteristics, laboratory parameters, and pathological diagnoses were collected retrospectively from electronic medical records. The pathological diagnosis was made by professional pathologists in keeping with relevant pathological guidelines, 18 and the results were classified in Table S1. Tumor markers such as alpha‐fetoprotein, carcinoembryonic antigen (CEA), and carbohydrate antigen 199 were included 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Details are not given on why, among the grossly visible preneoplastic lesions of the gallbladder, only PGA was placed outside of the ICPN in WHO 2019. However, one possible reason may be that PGA is relatively well-characterized as a neoplastic precursor gallbladder lesion and is more innocuous in behavior compared to other tumors categorized under ICPN [ 15 ], hence it is treated as an independent entity.…”
Section: Pyloric Gland Adenomamentioning
confidence: 99%